Simultaneous determination of Cd, Pb, and Cu in atmospheric particulate matter from different regions of the city of Presidente Prudente, Sao Paulo, Brazil - Proença, C. A. [UNESP]; Borsato, N. [UNESP]; Maroubo, L. [UNESP]; Moreira-Silva, M. R. [UNESP]; Gomes, H. M. [UNESP]; Teixeira, M. F.S. [UNESP] (Taylor & Francis, 2016)
This article explores the assessment of atmospheric deposition, from the analysis of the sampling methods, the analytical procedures for chemical characterisation of pollutants, and the main results from the scientific literature. Atmospheric particulate matter (PM) was collected in four regions of the city of Presidente Prudente (Sao Paulo State, Brazil) characterised by heavy traffic flows and high population density. The Cd, Pb, and Cu metals were determined in samples using differential pulse anodic stripping voltammetry. The PM was collected every fortnight using passive sampling, over a total period of two years. A comparative study between the element deposition fluxes in four sampling sites was performed. The relative contribution of the quantitative descriptors to divergence among the analysis by Tocher grouping method was also studied.
Keywords: atmospheric particulate; Metal deposition flux; Tocher method